THE PSYCHOEDUCATION OF LANGUAGE DISORDERS IN EARLY CHILDHOOD FOR PARENTS AND TEACHERS AT ECC DEWI SARTIKA MOJOKERTO - Aisyati, Wardah Wuri; Ika Ayuni Nurmaulidiya; Raisya Aulia; Waode Syaifatul Rohmadhani; Nur Ainy Fardana (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2024)
Introduction: Based on an initial survey conducted among parents, prospective parents, and educators at ECC Dewi Sartika, Mojokerto, it was found that 19% of people did not know about language disorders in early childhood. In addition, 29.3% of respondents did not know about the impact and urgency of handling language disorders in children. A total of 36.2% of respondents did not know about the symptoms or indications of language disorders in children, and as many as 58.6% of respondents did not know about how to treat children with language disorders, especially in early childhood. The purpose of  giving psychoeducation is increasing knowledge and attitude of those directly involved in the child's growth and development process, so they can find out an overview of the development of language and speech in children. Methods: The psychoeducation program is in the form of an interactive talk show conducted online through one of the video conference platforms. The target participants consisted of 8 teachers, 30 parents or caregivers, and 10 other parties who are directly or indirectly involved in the care and guidance of early childhood. Participants were given a pretest and post test to measure their knowledge and attitude towards language disorders in early childhood. The results obtained will be analyzed using a t-test with the Jamovi version 2.2.5 application. Results: The difference in the mean score is 16,842 (CI95 = [∞, 14,135]), the delivery of promotive interventions in the form of psychoeducation has a significant effect on increasing knowledge and attitudes towards language disorders in early childhood (t(48) = 10,495, p=<.001 , Cohen's d=1,702). Conclusion: This psychoeducation program is able to increase participants' understanding and attitude towards of language disorders in early childhood.